Healing at implant sites prepared conventionally or by means of Sonosurgery (R): an experimental study in dogs - Vigano, Paolo; Botticelli, Daniele [UNESP]; Salata, Luiz A.; Schweikert, Michael T.; Urbizo Velez, Joaquin; Lang, Niklaus P. (Wiley-Blackwell, 2015)
ObjectiveTo compare peri-implant tissue healing at implants installed in sites prepared with conventional drills or a sonic device.Material and methodsIn six Beagle dogs, the mandibular premolars and first molars were extracted bilaterally. After 3 months, full-thickness muco-periosteal flaps were elevated and recipient sites were prepared in both sides of the mandible. In the right side (control), the osteotomies were prepared using conventional drills, while, at the left side (test), a sonic device (Sonosurgery((R))) was used. Two implants were installed in each side of the mandible. After 8weeks of non-submerged healing, biopsies were harvested and ground sections prepared for histological evaluation.ResultsThe time consumed for the osteotomies at the test was more than double compared to the conventional control sites. No statistically significant differences were found for any of the histological variables evaluated for hard and soft tissue dimensions. Although not statistically significant, slightly higher mineralized bone-to-implant contact was found at the test (65.4%) compared to the control (58.1) sites.ConclusionsSimilar healing characteristics in osseointegration and marginal hard tissue remodeling resulted at implants installed into osteotomies prepared with conventional drills or with the sonic instrument (Sonosurgery((R))).
Keywords: Animal study; Bed preparation; Bone healing; Dental implants; Implant dentistry osteotomy; Soft tissue; Sonosurgery